FACTORS AFFECTING THE PERCEPTION OF INVESTORS TOWARDS EQUITY AND DERIVATIVES IN INDORE CITY - Gupta, Disha; Mokshmar, Priyanka (International Journal of Research -GRANTHAALAYAH, 2018)
Investment is referred as an activity on commitment on the funds available at present in any non-financial and financial instruments so as to receive the profitable return in the future. An investment is always done with particular objectives. As a matter of fact in investor who does not possess investment knowledge is only subconsciously allowed about the investment objective. This implies that there are a number of factors that affect the perception of investors towards investment. The perception of investor with respect to the decision about investment avenues is different in is dependent upon major demographic factors like income, age, social needs and experience. This paper aims to analyse the factors that affect the perception of investors towards equity and derivatives in Indore city. The study employs primary data in a number of factors affecting the perception of investors towards equity and derivatives are revealed.